Lactobacillus plantarum ZJUFB2 Prevents High Fat Diet-Induced Insulin Resistance in Association With Modulation of the Gut Microbiota - Zhong, Hao; Wang, Jian; Abdullah,; Hafeez, Muhammad Adnan; Guan, Rongfa; Feng, Fengqin (Frontiers in Nutrition, 2021)
Lactobacillus plantarum ZJUFB2 (B2), a novel probiotic isolate derived from Chinese traditional sourdough, possesses promising probiotics properties. This study aimed to investigate the effects of B2 on the insulin sensitivity using mice fed on high-fat diet (HFD) as well as to explore the involved mechanisms. Purposely, male C57BL/6 mice continuously received an intervention of B2 (~109 CFU/d) for 16 weeks. Results showed that B2 treatment remarkably ameliorated the insulin resistance and hyperglycemia in HFD-fed mice. The B2 intervention significantly decreased the hepatic lipid accumulation, serum low density lipoproteins cholesterol and lipopolysaccharides, and regulated the bile acids levels as well as liver mRNA expression involved in lipid metabolism. Moreover, B2 intervention significantly changed the gut microbiota, specifically, showed a lower abundance of obesity-related and inflammation-associated microbes, Ruminococcaceae, Lactobacillaceae, Desulfovibrionaceae, Lachnospiraceae and Mogibacteriaceae, and a higher abundance of short-chain fatty acids and bile salt hydrolase producing bacteria, such as Bifidobacteriaceae, Helicobacteraceae and Deferribacteraceae compared to the HFD group. The study findings inferred that B2 is a novel, safe and an effective probiotic which could be used in preventing insulin resistance by improving the gut microbiota and bile acids.